Diversity and characterization of native maize from the “El Cielo” Biosphere Reserve, Tamaulipas, Mexico - González-Martínez, Javier (Universidad Autónoma de Tamaulipas, 2019)
The diversity of maize in Mexico is based on the presence of breeds that range from 59 to 64 varieties. Tamaulipas is a corn-producing state that contributes to sustain this enormous variation of breeds, especially in isolated regions. The biosphere ecological reserve “El Cielo” is located in a mountainous region, which comprises Jaumave, Ocampo, Gómez Farías and Llera de Canales municipalities. This region has been scarcely studied in spite of the degradation or extinction risks of native populations of maize due to factors such as changes in land use and natural phenomena. The objective of this work was to analyze the morphologic diversity of native maize varieties of “El Cielo” biosphere ecological reserve. Native maize harvests were collected in the municipalities that comprise the reserve during the months of February, March and April of 2016. The sample size ranged between 20 and 30 cobs of each variety, out of this sample 10 cobs were selected in order to register quantitative and qualitative variables. A multivariate analysis method of main components and conglomerates was used. Results show that 62.45 % of the samples were correspondent with total variation, which was explained by the first two main compo- nents. The variables with greater contribution to the variation were cob length, number of grains per row, cob weight, weight and volume of 100 grains, cob diameter, number of rows per hob and the relation of diameter/length in each cob. The native maize populations that are still cultivated at the biosphere ecological reserve “El Cielo” there was a wide morphological diversity of cob, as well as variation in the com- bination of grain and corncob color. This suggests that native populations possess a substantial potential as a gene pool and gene reservoir.